Concepções e práticas de professoras sobre o erro e a dificuldade de aprendizagem em matemática de alunos do 5º ano do ensino fundamenta l : encontros e desencontros - Pizaneschi, Fabiane Passarini Marques (2017)
Our research investigates the conceptions and the practices of teachers between the error and the learning difficulties in mathematics and the treatment and relation given to both in the teaching-learning process of 5th grade elementary school students. The research is configured in a qualitative approach on which we are theoretically based on Bogdan and Biklen (1994), Ludke and André (2012) Fiorentini and Lorenzato (2006). To answer our research problem, we defined as a survey context, 01 state school of Cuiabá-MT city, located in the urban zone, which will be called Cora Coralina School. We chose as our research subjects, 02 mathematics teachers of the 5thgrade of elementary participant school. We used as instruments of data production, characterization questionnaires of the school, of the teachers and mixed ones, that were divided in three parts, (teaching-learning conceptions, the error in mathematics teaching and learning difficulties). The field research embraced classroom observations, field journal, (observed facts systematization during the period in classroom) semi-structured interviews and the Political Pedagogical Project (PPP). To discuss about the teaching-learning process we resorted to the following theorists: Mizukami (1986); Ponte (1994); Becker (1993); Darsie (1999), among others. In order to deal with the error and learning difficulties in mathematics learning process, we dialoguewith Pinto (2009); Abrahão (2007); Davis (1990); Macedo (1994) among others. For data analysis and interpretation, we develop three analysis categories from the mentioned theoretical reference and data collected: Teachers conceptions and practices; the treatment given to errors and mathematics learning difficulties- MLD, errors and mathematics learning difficulties- MLD: Meetings and mismatches. The data analysis allows us to consider that the teaching-learning conceptions and practices of the research participating teachers vary and are delimitated sometimes for the reflective perspective and sometimes for the exclusionary learning perspective, such conceptions reflect on the way teachers consider the error and the MLD. From the researched teachers' conceptions, about the treatment given to the error and the learning difficulty, we could verify two perspectives. The first one that mutes and eliminates the error and the MLD from the learning process, treating them as an obstacle in the development of the students’ intellect, with MLD rarely being treated in the classroom; and the second one, that conceives the error as a pedagogical component inherent in the student's process of knowledge construction. , provoking reflections about the hypotheses elaborated by students, which is examined and exploited in its didactical potential. The teachers understand that the errors and the MLD occur for different reasons, not establishing a direct relationship between them. Understanding the error as an integral part of teaching and learning Mathematics remains a challenge in teaching practice.